Forced Migration Governance in Southeast Asian Countries: ‘Same but Different’? - Muhammad Riza Nurdin; Mala Rajo Sathian; Hanafi Hussin (Otoritas : Jurnal Ilmu Pemerintahan, 2020)
This paper examines the governance of forced migration in Southeast Asia. The region hosts about 2.5 million of forcibly displaced migrants from a worldwide total of 70 million (2018). The migrants include intra- ASEAN and non-ASEAN refugees or asylum seekers, notably from the Middle East.  Based on a review of recent literature, the paper investigates three main destination states in SEA that host the majority of the forced migrants; Indonesia, Malaysia, and Thailand. The paper examines (i) local policies in the governance of forced migrants and (2) the practice of non-refoulement principle. The findings reveal that in terms of forced migration governance, Indonesia, Malaysia, and Thailand are ‘same but different'; meaning that despite being similar, each country produces different outcomes.